Influence of phenolic compounds on the growth and arginine deiminase system in a wine lactic acid bacterium - Alberto, Maria Rosa (2012)
The influence of seven phenolic compounds, normally present in wine, on the growth and arginine deiminase system (ADI) of Lactobacillus hilgardii X1B, a wine lactic acid bacterium, was established. This system provides energy for bacterial growth and produces citrulline that reacts with ethanol forming the carcinogen ethyl carbamate (EC), found in some wines. The influence of phenolic compounds on bacterial growth was compound dependent. Growth and final pH values increased in presence of arginine. Arginine consumption decreased in presence of protocatechuic and gallic acids (31 and 17%, respectively) and increased in presence of quercetin, rutin, catechin and the caffeic and vanillic phenolic acids (between 10 and 13%, respectively). ADI enzyme activities varied in presence of phenolic compounds. Rutin, quercetin and caffeic and vanillic acids stimulated the enzyme arginine deiminase about 37-40%. Amounts of 200 mg/L gallic and protocatechuic acids inhibited the arginine deiminase enzyme between 53 and 100%, respectively. Ornithine transcarbamylase activity was not modified at all concentrations of phenolic compounds. As gallic and protocatechuic acids inhibited the arginine deiminase enzyme that produces citrulline, precursor of EC, these results are important considering the formation of toxic compounds.